P14.18 Prognostic value of serial dynamic O-(2-[18F]-fluoroethyl)-L-tyrosine PET in patients with non-resectable malignant glioma undergoing chemoradiation. (6th September 2019) - Rosen, J; Stoffels, G; Lohmann, P; Bauer, E K; Werner, J; Rapp, M; Felsberg, J; Fink, G R; Langen, K; Galldiks, N
Abstract: BACKGROUND: A complete resection of high-grade gliomas (HGG) is associated with improved survival, which, however, cannot be achieved in a considerable number of patients. We here evaluated the prognostic value of serial O -(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) PET in patients with newly diagnosed, non-resectable astrocytic HGG undergoing chemoradiation with temozolomide. MATERIAL AND METHODS: Serial dynamic FET PET scans were performed in 18 newly diagnosed patients with molecularly defined, non-resectable HGG at baseline and after chemoradiation (8±3 weeks). Both static (tumor/brain ratios, FET tumor volumes) and dynamic FET PET parameters (time-to-peak, slope), as well as MRI changes according to RANO criteria at first follow-up after chemoradiation (8±3 weeks), were obtained. The predictive ability of FET PET parameters and RANO criteria was evaluated with regard to the progression-free survival (PFS). Using ROC analyses, threshold values for FET PET parameters were obtained. Subsequently, univariate and multivariate survival analyses were performed to assess their predictive power for PFS. RESULTS: ROC analysis revealed that the mean tumor/brain ratio (AUC, 0.84), FET tumor volume (AUC, 0.89), and slope (AUC, 0.72) at baseline were predictive for a prolonged PFS (9.3 vs. 5.7 months, P=0.05; 10.3 vs. 5.9 months; P=0.03; 13.5 vs. 6.2 months, P=0.02, respectively). Furthermore, FET tumor volume and slope remained significant in the multivariate survival analysis (both P<0.05). In contrast, relative changes of static or dynamic FET PET parameters at follow-up and MRI changes according to RANO criteria were not significant in this albeit small series of patients. CONCLUSION: Results suggest that before initiation of chemoradiation FET PET parameters at baseline can be used to predict PFS in patients with non-resectable HGG.